Artroskopická subtalární distrakční artrodéza v poúrazových indikacích - Rak, Václav; Šrámek, Jakub; Ira, Daniel; Krtička, Milan (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2024)
PURPOSE OF THE STUDY: This manuscript aims to present the method of arthroscopic assisted subtalar arthrodesis and to evaluate the benefi ts of this surgery on our study population. MATERIAL AND METHODS: In the period from 9/2007 to 1/2020, a total of 33 subtalar arthrodesis were performed in 31 patients aged 19-66 years (mean 48 years, median 50 years). The indication for arthrodesis was subtalar arthritis causing pain and gait disorders, or hindfoot deformities (most commonly after a calcaneus bone fracture). The arthroscopic assisted subtalar arthrodesis was performed with autologous tricortical bone block graft harvesting from the pelvis, supplemented by autologous cancellous bone graft. Stabilization was achieved by cannulated screws inserted in neutral ankle position. Patients in our retrospective study were followed up for a mean of 48 months (range, 24-130 months). The patients were evaluated preoperatively and at 2 years after surgery. The hindfoot angles and height (TCA - talocalcaneal angle, CIA - calcaneal inclination angle, TCH - talocalcaneal height) were evaluated on radiographs, bone union was assessed on radiographs and CT scans. The clinical assessment was performed using the ankle-hindfoot scale (AHS) of AOFAS (AOFAS score). RESULTS: The preoperative AOFAS score was 35-68 points (mean 52, median 54), the postoperative AOFAS score at 2 years after arthrodesis was 58-94 points (mean 82, median 82). Both the mean and median values of AOFAS score showed a signifi - cant progress from the poor result to the good and excellent result. After 2 years the TCA value decreased in 18 patients (56%) by no more than 3°. The CIA decrease observed in 21 patients (64%) was by 1° on average. The TCH decrease of 1-5 mm after 2 years since the surgery was seen in 16 patients. In 2 patients incomplete healing of arthrodesis was observed, manifested as a clinically asymptomatic non-union. No deep infection was reported. DISCUSSION: In agreement with the current literature, the arthroscopic subtalar arthrodesis has been confi rmed to be a safe method for the management of consequences of hindfoot fractures, with minimum complications and leading to accelerated bone fusion. Differences can be found in the approach, position, use of cancellous bone graft and surgical techniques. In recent years, prone position, posterior approaches, use of cancellous bone graft, distraction and fi xation with 2-3 screws divergently inserted into the bone prevail. The degree of healing of the bone fusion is generally an important factor. In our study population, non-healing was recorded in 2 patients, namely in the form of a clinically silent non-union. Neurological or early complications and/or osteosynthesis material failure occurred in up to a maximum of 10% of cases. The conclusive results of minimally invasive arthrodesis based on the AOFAS score have been confi rmed by us as well as by most authors. CONCLUSSIONS: Our study confi rmed that the arthroscopic assisted subtalar arthrodesis is a successful, reliable and safe minimally invasive method, with minimum complications, leading to stable arthrodesis. KEY WORDS: subtalar arthrodesis, subtalar arthroscopy.
Keywords: artrodéza; Foot; Calcaneus; fraktury kostí; noha (od hlezna dolů); patní kost; retrospektivní studie; lidé; poranění kotníku; Fractures, Bone; Arthrodesis; Ankle Injuries; Retrospective Studies; dolní končetina; Lower Extremity; Humans